Les dépotoirs de céramiques de Thelepte, productions locales et produits importés - Nasr, Mongi (Rei Cretariae Romanae Fautorum Acta, 2022)
The archaeological site of Thelepte, in west-central Tunisia, covers more than 94 ha and contains innumerable archaeological remains, including traces of kilns and ceramic deposits. The understanding of the material of the latter is difficult because of its heterogeneity as well as the double nature of this site, both producer and importer of ceramics, in particular African Red Slip Wares. However, the great similarities between regional and/or local productions and their quantitative importance within the material studied, allowed us to perform petrographic analyses in order to detect the local production of Thelepte, to determine its characteristics and to distinguish it both from other regional productions, namely that of Sidi Aïch, as well as so-called ‘classic’ or ‘universal’ productions.